Adolescent exposure to violence and adult illicit drug use. (April 2015) - Menard, Scott; Covey, Herbert C.; Franzese, Robert J.
Abstract: Informed by a strain theory perspective, this study utilizes data on adolescent exposure to violence (AEV) from a prospective, longitudinal, national household probability sample that originally consisted of 1, 725 respondents, first interviewed as adolescents in 1977 and last interviewed in middle adulthood in 2003. Findings from bivariate correlations and logistic regression models indicate that AEV is associated with both adolescent and adult illicit drug use, but some of the association between AEV and adult illicit drug use becomes nonsignificant when controlling for adolescent illicit drug use. Specific types of AEV associated with adult illicit drug use differ by gender. Implications, limitations, and future research directions are discussed.